helppppppppp pfvvvv
Anexos:
![](https://pt-static.z-dn.net/files/d85/e5b8d0c87684551f0fd0f0b2454be3df.jpg)
Soluções para a tarefa
Respondido por
1
Resposta:
e
Explicação passo-a-passo:
(a-8b)/3ab . -4/-4=-4(a-8b)/-4.3ab=(-4a+32b)/-12ab
se você quiser confirmar, suponha a=b=1
(a-8b)/3ab=(1-8.1)/3.1.1=-7/3
(-4a+32b)/-12ab=(-4.1+32.1)/-12.1.1=(-4+32)/-12=28/-12=-7/3
Perguntas interessantes
Geografia,
10 meses atrás
Sociologia,
10 meses atrás
Biologia,
10 meses atrás
Química,
1 ano atrás
Matemática,
1 ano atrás
Português,
1 ano atrás